Toward a Better Future : Education and Training for Economic Development in Singapore since 1965 - Lee, Sing-Kong; Goh, Chor Boon; Fredriksen, Birger; Tan, Jee Peng (Washington, DC : World Bank, 2012)
The Singapore economy has undergone significant stages of development since the 1960s. It has grown from its traditional role as a regional port and distribution center in the 1960s to an international manufacturing and service center in the 1970s and 1980s, and now into a center of science-based manufacturing and knowledge-intensive technical services. Much has been written to explain this success. Emphasis has been placed on the early adoption of an export-oriented strategy for industrialization, high savings and investment rates, a stable macroeconomic environment, and even socio cultural traits that support successful industrialization. This volume documents a less-explored aspect of Singapore's economic development: it examines the transformation of the education and training system since the country's independence in 1965 and how the process contributed to skills formation and, hence, economic change.